Macrophages in neuroinflammation: role of the renin-angiotensin-system - Hammer, Anna; Stegbauer, Johannes; Linker, Ralf (Pflügers Archiv: European Journal of Physiology, 2017)
Macrophages are essential players of the innate immune system which are involved in the initiation and progression of various inflammatory and autoimmune diseases including neuroinflammation. In the past few years, it has become increasingly clear that the regulation of macrophage responses by the local tissue milieu is also influenced by mediators which were first discovered as regulators in the nervous or also cardiovascular system. Here, the renin-angiotensin system (RAS) is a major focus of current research. Besides its classical role in blood pressure control, body fluid, and electrolyte homeostasis, the RAS may influence (auto)immune responses, modulate T cells, and particularly act on macrophages via different signaling pathways. Activation of classical RAS pathways including angiotensin (Ang) II and AngII type 1 (AT1R) receptors may drive pro-inflammatory macrophage responses in neuroinflammation via regulation of chemokines. More recently, alternative RAS pathways were described, such as binding of Ang-(1-7) to its receptor Mas. Signaling via Mas pathways may counteract some of the AngII/AT1R-mediated effects. In macrophages, the Ang-(1-7)/Mas exerts beneficial effects on neuroinflammation via modulating macrophage polarization, migration, and T cell activation in vitro and in vivo. These data delineate a pivotal role of the RAS in inflammation of the nervous system and identify RAS modulation as a potential new target for immunotherapy with a special focus on macrophages.
EVALuna2:22498